2020
DOI: 10.3389/feduc.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Mediation, Emotional Regulation and Coping Strategies in the Educational Field

Abstract: Teachers who present high emotional skills and knowledge of strategies to mediate the conflicts generated in the classroom, are able to exercise a better management of both the teaching tasks that correspond to them and to establish an emotionally nutritive and productive educational climate for the students. This research aims to study and analyze, under an integrative conceptual revision methodology, the theories and models that consider individual, group and social aspects of the origin, development and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
0
9
0
4
Order By: Relevance
“…On the other hand, we tested the effects of the intervention on MC variables. In this sense, results showed that the presence of MCs significantly decreased over time, both for MCs with teammates (χ 2 [df] = 11.143 [2], p = 0.004) and with opponents (χ 2 [df] = 20.326 [2], p < 0.001). In addition, we tested for possible differences on students' perceptions of the intensity of MCs.…”
Section: Effects Of the Interventionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, we tested the effects of the intervention on MC variables. In this sense, results showed that the presence of MCs significantly decreased over time, both for MCs with teammates (χ 2 [df] = 11.143 [2], p = 0.004) and with opponents (χ 2 [df] = 20.326 [2], p < 0.001). In addition, we tested for possible differences on students' perceptions of the intensity of MCs.…”
Section: Effects Of the Interventionmentioning
confidence: 99%
“…In addition, it is necessary to identify what attitude the two parties have adopted in dealing with the conflict, e.g., competitive (win-lose), avoidant (lose-lose), or submissive (lose-win) attitudes [86,87]. The pedagogical intervention will attempt to teach students to learn to transform the adopted attitudinal style towards the model of collaboration between equals (win-win) characterised by dialogue, respect towards peers and/or opponents together with compliance with the rules of the game [2,88,89].…”
Section: Part 2: Evaluation Of Motor Conflictsmentioning
confidence: 99%
See 2 more Smart Citations
“…Events associated with emotions are easier to recall and last longer in one's memory (Mora, 2016). But the study of emotions, their application in the classroom, and the need for the existence of a good classroom climate for a beneficial, motivating and interesting educational process has not been sufficiently studied (Garritz, 2009), despite the need for teachers to carry out good emotional management and to possess strategies for resolving conflicts (Bonilla et al, 2020). What we know today is that teachers with high levels of stress reported also higher levels of anxiety and depression and that may also influence the student's affective experience in learning (Poon et al, 2019) but also a positive association between teachers and students positive emotions have been found in science lessons (Frenzel et al, 2009).…”
Section: Emotions In Teaching and Learningmentioning
confidence: 99%